A clinical-stage Nrf2 activator suppresses osteoclast differentiation via the iron-ornithine axis - Dong, Yimin; Kang, Honglei; Peng, Renpeng; Liu, Zheming; Liao, Fuben; Hu, Shi-an; Ding, Weizhong; Wang, Pengju; Yang, Pengchao; Zhu, Meipeng; Wang, Sibo; Wu, Minglong; et al. (Cell metabolism, 2024)
Activating Nrf2 by small molecules is a promising strategy to treat postmenopausal osteoporosis. However, there is currently no Nrf2 activator approved for treating chronic diseases, and the downstream mechanism underlying the regulation of Nrf2 on osteoclast differentiation remains unclear. Here, we found that bitopertin, a clinical-stage glycine uptake inhibitor, suppresses osteoclast differentiation and ameliorates ovariectomy-induced bone loss by activating Nrf2. Mechanistically, bitopertin interacts with the Keap1 Kelch domain and decreases Keap1-Nrf2 binding, leading to reduced Nrf2 ubiquitination and degradation. Bitopertin is associated with less adverse events than clinically approved Nrf2 activators in both mice and human subjects. Furthermore, Nrf2 transcriptionally activates ferroportin-coding gene Slc40a1 to reduce intracellular iron levels in osteoclasts. Loss of Nrf2 or iron supplementation upregulates ornithine-metabolizing enzyme Odc1, which decreases ornithine levels and thereby promotes osteoclast differentiation. Collectively, our findings identify a novel clinical-stage Nrf2 activator and propose a novel Nrf2-iron-ornithine metabolic axis in osteoclasts. [Display omitted] •Bitopertin is a clinical-stage Nrf2 activator to ameliorate bone loss•Bitopertin has fewer adverse events than clinically approved Nrf2 activators•Nrf2 inhibits osteoclastogenesis by activating Slc40a1 and decreasing iron levels•Nrf2 knockout or iron supplementation reduces ornithine levels via upregulating Odc1 Dong et al. identified a clinical-stage novel Nrf2 activator that suppresses osteoclast differentiation and ameliorates estrogen-depletion-induced bone loss via a novel Nrf2-iron-ornithine pathway. In human subjects, this activator has fewer adverse events than existing clinical Nrf2 activators and may be a candidate of Nrf2 activators for clinical use.